Protective effect of exercise and sildenafil on acute stress and cognitive function - AKAKIN, DİLEK; ÖZBEYLİ, DİLEK; YÜKSEL, MERAL; KASIMAY ÇAKIR, ÖZGÜR (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Introduction: There are contradictory results about the effects of exercise and sildenafil on cognitive functions. Aim: To investigate the effects of sildenafil pretreatment and chronic exercise on anxiety and cognitive functions. Method: Wistar rats (n = 42) were divided as sedentary and exercise groups. A moderate-intensity swimming exercise was performed for 6 weeks, 5 days/week, 1 h/day. Some of the rats were administered orogastrically with sildenafil (25 mg/kg/day) either acutely or chronically. Exposure to cat odor was used for induction of stress. The level of anxiety was evaluated by elevated plus maze test, while object recognition test was used to determine cognitive functions. Brain tissues were removed for the measurement of myeloperoxidase (MPO), malondialdehyde (MDA), nitric oxide levels, lucigenin-enhanced chemiluminescence, and for histological analysis. Results: Increased MPO and MDA levels in sedentary-stressed rats were decreased with sildenafil applications. Chronic exercise inhibited the increase in MPO levels. Increased nitric oxide and lucigenin chemiluminescence levels in sedentary-stressed rats, were diminished with chronic sildenafil pretreatment. The time spent in the open arms of the plus maze was declined in sedentary-stressed rats, while chronic sildenafil pretreatment increased the time back to that in non-stressed rats. Acute sildenafil application to exercised rats prolonged the time spent in open arms as compared to non-treated exercise group. The time spent with the novel object, which was decreased in sedentary-stressed rats, was increased with sildenafil pretreatment. Our results suggest that sildenafil pretreatment or exercise exerts a protective effect against acute stress and improves cognitive functions by decreasing oxidative damage. (C) 2015 Elsevier Inc All rights reserved.
Keywords: Chronic exercise; Sildenafil; Acute stress; ANXIETY-LIKE BEHAVIOR; OXIDATIVE STRESS; AEROBIC EXERCISE; PSYCHOLOGICAL STRESS; PHYSICAL-FITNESS; OBJECT MEMORY; ODOR ELICITS; BRAIN; INJURY; MICE